Penerapan Ultrasound Dan Stretching Exercise Pada Kasus Fasciitis Plantaris Sinistra Di RST Dr. Soedjono Magelang - Hasanah, Uswatun; , Arif Pristianto, SSt.FT.,M.Fis (2017)
Background: Plantaris fasciitis is an inflammatory condition of plantile aponeurosis that cauces pain along the plantar fascia. The factors is trigger the occurence of plantar fascia are biomechanical factor, overuse and repetitive injury to the plantar fascia. Complaints that often arise in case of plantar fasciitiis and stretching exercise modality is applied in order to reduce complains of pain and decreased scope of joint motion in patients. Objective: To determine the benefits of ultrasound and stretching exercise in reducing pain and increasing the scope of joint motion in the condition of patient with plantar fasciitis complaints. Result: After six therapeutic measures with ultrasound modalitiy and stretching exercise in patient with plantar fasciitis complaints resulted in decreased pain T: 0 cm, T6: 0cm, pain press T1: 6,9 cm, to T6: 2,5 cm, motion pain: 5,9 cm, become T6: 1,4 cm. Increased scope of joint motion of the left ankle T1: (S) 20-0-35, become T6: 20-0-45, (R) 15-0-35. Clonclusions: Ultrasound and stretching exercise can reduce pain and increase the scope of joint motion under conditions of plantar fasciitis.